Crucifixion in the Mediterranean world - Cook, John Granger (Wissenschaftliche Untersuchungen zum Neuen Testament, 2014)
To understand the phenomenon of Roman crucifixion, John Granger Cook argues that one should begin with an investigation of the evidence from Latin texts and inscriptions (such as the lex Puteolana [the law of Puteoli]) supplemented by what may be learned from the surviving archaeological material (e.g., the Arieti fresco of a man on a patibulum [horizontal beam], the Puteoli and Palatine graffiti of crucifixion, the crucifixion nail in the calcaneum bone from Jerusalem, and the Pereire gem of the crucified Jesus [III CE]). This evidence clarifies the precise meaning of terms such as patib